Repeated Interactions and Contractual Detail: Identifying the Learning Effect - Vanneste, Bart S.; Puranam, Phanish (Organization Science, 2010)
Organizations interacting repeatedly on similar transactions may learn from prior experiences, allowing contracts to be specified in greater detail. In this study, we analyze the conditions under which this learning effect is most likely to manifest itself. We do this by focusing on different parts of a contract as well as differences across transacting parties. Using a survey of information technology procurement contracts from 788 Dutch small- and medium-sized enterprises, we show that the learning effect is stronger for technical than for legal detail in contracts and is stronger for firms with information technology expertise than for firms without such expertise.